Equity impacts of price policies to promote healthy behaviours. Issue 10134 (19th May 2018) - Sassi, Franco; Belloni, Annalisa; Mirelman, Andrew J; Suhrcke, Marc; Thomas, Alastair; Salti, Nisreen; Vellakkal, Sukumar; Visaruthvong, Chonlathan; Popkin, Barry M; Nugent, Rachel
Summary: Governments can use fiscal policies to regulate the prices and consumption of potentially unhealthy products. However, policies aimed at reducing consumption by increasing prices, for example by taxation, might impose an unfair financial burden on low-income households. We used data from household expenditure surveys to estimate patterns of expenditure on potentially unhealthy products by socioeconomic status, with a primary focus on low-income and middle-income countries. Price policies affect the consumption and expenditure of a larger number of high-income households than low-income households, and any resulting price increases tend to be financed disproportionately by high-income households. As a share of all household consumption, however, price increases are often a larger financial burden for low-income households than for high-income households, most consistently in the case of tobacco, depending on how much consumption decreases in response to increased prices. Large health benefits often accrue to individual low-income consumers because of their strong response to price changes. The potentially larger financial burden on low-income households created by taxation could be mitigated by a pro-poor use of the generated tax revenues.